Beyond Technical Efficiency: Integrating Islamic Reflective Pedagogy into Digital Learning Design - Mu’in Abdullah; Sukari Sukari (Assyfa Journal of Islamic Studies, 2025)
In today's rapidly evolving digital era, critical thinking skills, ethical literacy, and independent learning have become essential competencies for students, where reflective and dialogical pedagogy-based teaching is seen as the most effective creative strategy for fostering depth of meaning. This research is motivated by the phenomenon of the transformation of Islamic education (tarbiyah) pedagogy, which tends to be trapped in the mechanical adoption of technology. Meanwhile, Islamic education research has largely evaluated the effectiveness of media on students' cognitive and motor skills without addressing the deeper spiritual dimension. The primary objective of this research is to formulate an integrative framework that synergizes digital innovation with Islamic values ​​to ensure the sustainability of character development in cyberspace. Using qualitative methods through a conceptual-analytical study design and a systematic literature review of journals and education policy documents, data were analyzed thematically to map gaps in contemporary practices. The results reveal that current digital learning is still dominated by a technical-instrumental approach, which results in superficial internalization of values. Learning designs that are not value-oriented fail to significantly shape students' moral integrity. The findings indicate that scaffolding through the educator's role as a facilitator of meaning and value guidance is more influential than the sophistication of the technology itself. In conclusion, integrating Islamic values ​​into digital learning design innovations is not simply a methodological choice, but a moral and pedagogical imperative to create humanistic, relevant, and meaningful education in the digital age.